Willingness to Communicate in English among ESL Undergraduates in Malaysia - Ai Seok, KHO-YAR; Shameem, RAFIK-GALEA; Elise Ai, Hwee KHO (UNIMAS Publisher, 2018)
Students’ unwillingness in communicating (WTC) English has many factors especially in second language acquisition. This study investigates the willingness to communicate (WTC) in English among ESL undergraduates in Malaysia. A hypothesised model that integrates WTC in English, motivation, self-efficacy, mindset, and performance was tested using structural equation modelling (SEM). The results show that the personality of learners are directly affecting motivation and WTC in English. Further, the results also demonstrate that both motivation and academic achievement influences WTC in English indirectly through self-efficacy. The final model correlates well with the data, thereby indicating the potential of academic achievement can contribute to ESL communication.